2014
DOI: 10.3762/bjnano.5.20
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of carbon nanomembranes by helium ion beam lithography

Abstract: SummaryThe irradiation-induced cross-linking of aromatic self-assembled monolayers (SAMs) is a universal method for the fabrication of ultrathin carbon nanomembranes (CNMs). Here we demonstrate the cross-linking of aromatic SAMs due to exposure to helium ions. The distinction of cross-linked from non-cross-linked regions in the SAM was facilitated by transferring the irradiated SAM to a new substrate, which allowed for an ex situ observation of the cross-linking process by helium ion microscopy (HIM). In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…Thus, the use of FEBID and FIBID at room temperature presents limitations in speed or causes damage that hampers a broader use. In Figure 7, another example of a single-step resist-free charge-based nanolithography technique is included, that of the formation of ultra-thin carbon membranes from the exposure of self-assembled monolayers (SAM), which require at least 850 µC/cm 2 [75]. As shown in Figure 7, the use of Cryo-FEBID and Cryo-FIBID opens new opportunities due to the lower area charge dose required.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the use of FEBID and FIBID at room temperature presents limitations in speed or causes damage that hampers a broader use. In Figure 7, another example of a single-step resist-free charge-based nanolithography technique is included, that of the formation of ultra-thin carbon membranes from the exposure of self-assembled monolayers (SAM), which require at least 850 µC/cm 2 [75]. As shown in Figure 7, the use of Cryo-FEBID and Cryo-FIBID opens new opportunities due to the lower area charge dose required.…”
Section: Discussionmentioning
confidence: 99%
“…ions than for electrons. Zhang et al attribute this to a higher SE yield and an SE energy distribution that is shifted to lower energies [60]. More experimental evidence is needed to determine whether this is indeed correct.…”
Section: Comparison To Ion Beam Lithographymentioning
confidence: 83%
“…For He ? ions, the higher deposition yield (compared to deposition with electrons) is possibly due to a higher SE yield [60]. When cross-linking self-assembled monolayers, the dose to fully cross-link the layer is about 609 lower for He ?…”
Section: Comparison To Ion Beam Lithographymentioning
confidence: 99%
“…a, (ii)). It has been demonstrated that crosslinking of aromatic SAMs can also be achieved via He + ion and UV/extreme UV irradiation as well as electron irradiation with significantly higher in the range of keV electron energies . However, low energy electrons generated during these different types of irradiation were identified as the main reason for the observed modification.…”
Section: Conversion Of Aromatic Sams Into Cnmsmentioning
confidence: 99%